Unwritten flaws of Indian bureaucracy - Sahu, Barun Kumar (Delhi, 2004)
This book provides unconventional insights into inscrutable public (even private!) bureaucracies, where chaos is the order of the day and imperfection the ubiquitous pattern.
Keywords: Bureaucracy